Uso Pedagógico Das Tdic: Estudo De Caso Da Formação Continuada De Professores Em Serviço, Em Uma Escola Municipal Da Zona Leste De São Paulo - Santos, Geane Carneiro [UNIFESP] (2017)
This research is in the field of public policies and teacher training. It is an educational case study, under the qualitative methodological approach of a descriptive character. The general objective is to analyze and understand the contribution of a continuing in service training course imbricated to the pedagogical use of Digital Information and Communication Technologies (TDIC) in a municipal school in the east of São Paulo. The research is based on the following theoretical reference framework: approaches to the educational use of TDICs (VALENTE, 2002, UNESCO, 2009); Digital literacy and shared mediation (PESCE and BRUNO, 2012); Collaborative learning (BELLONI and GOMES, 2008); Revitalization of study time as a space for collective and collegial discussion and planning (NÓVOA, 1999; DAVIS, 2012); Empowerment (FREIRE, 2001b; 2003); (Freire and Shor, 2001). In the characterization of the research corpus is presented the research locus, the historical panel of the Educational Informatics Program, in the Municipal Education Network of São Paulo, and the figure of the Educational Informatics Counselor (POIE), as trainer in the school. The instruments of data collection were the Political Educational Project (PPP) and two questionnaires applied before and after the training and semi-structured interview, which sought to: i) raise the profile of the participants of the training; Ii) analyze the context of the TDIC in the PPP of the school; Iii) to know the pedagogical practices of the faculty, considering the limits and possibilities of the school, regarding the use of digital media. The documentary analysis of the PPP found that the document has few notes regarding the use and possible contributions of the TDIC in educational practices, restricting them to mere pedagogical tools linked to the work developed by POIE in the computer lab. The thematic content analysis derived from participants testimonies suggests that the teaching group participating in the training value the collective study time in the school, viewing it as a moment of formation, interactions and exchanges of experiences. The training was fruitful in the empowerment process (in the Freirean sense) of the group, contributing to the appropriation and critical-reflexive use of digital media, including collaborative practices between teachers and POIE. Infrastructure and lack of time for planning are the main limits pointed out by the group so that individual and collective practices with the pedagogical use of TDIC become effective.